(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2024)
Holy Scripture: Part of Divine Revelation and Its Relevance in the Context of Global Crises.God’s revelation, one of the main themes in Christianity is actually the fundamental of Christian belief and principles. The purpose of this paper is to analyze the Word of God - the Bible as the revelation available to people nowadays. I will try to prove that its place is in the public space and taking in consideration the global crises circumstances, it is a must to know the reveled truth. Despite its considerable antiquity, the Word of Holy Scripture stays relevant in society even today. We will find a lot of answers to all humankind existential questions by reading the Bible. The Word has the power to transform people and give them a new meaning in life. The resistance of the Bible to the changes that have taken place in the world demonstrates its divine nature and the power that springs from revealed truth. In this article, the author studies the Bible as a part of God’s revelation. By highlighting this, the sacred writings are given normative value, being beneficial to all who apply them in their life. It is emphasized that both history and logic demonstrate that the evolution of society is closely related o the religious context, the first promoters in science being faithful people ho used the Bible as a guide for their life. In the context of major global crises, the Bible values are essential in order to resolve and reduce the negative effects around the world. The values of the Bible are transcendent and bring benefits to all communities of believers who have chosen to lead their lives according to the divine principles, allowing themselves to be shaped by the truth revealed in the Holy Scripture.